Targeting intracellular galectins for cancer treatment - Nehmé, Rita; St-Pierre, Yves (Frontiers in Immunology, 2023)
Although considerable attention has been paid to the role of extracellular galectins in modulating, positively or negatively, tumor growth and metastasis, we have witnessed a growing interest in the role of intracellular galectins in response to their environment. This is not surprising as many galectins preferentially exist in cytosolic and nuclear compartments, which is consistent with the fact that they are exported outside the cells via a yet undefined non-classical mechanism. This review summarizes our most recent knowledge of their intracellular functions in cancer cells and provides some directions for future strategies to inhibit their role in cancer progression.